PENGARUH KUALITAS AUDITOR, DEBT DEFAULT, OPINION SHOPPING, OPINI AUDIT TAHUN SEBELUMNYA DAN REPUTASI KAP TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN (Studi Empiris Pada Perusahaan Manufaktur di BEI) - Kharisma Rianto; Amir Hasan; Al Azhar A ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this research is to examine as empirically the effect of relevant variables that affect a company engaged in the manufacturing of the audit opinion given by the Going Concern auditor.Data collected by way of technical documentation, namely to collect the document that has occurred (financial statements and audit company) or corporate documents in accordance with the necessary data. The population in this study are all companies engaged in manufacturing that were listed on the Stock Exchange (Indonesia Stock Exchange) in 2011 until 2013. While the total sample of 54 manufacturing companies chosen by purposive sampling. The analytical method used in this research is the logistic regression with SPSS 17.00.From the results of the study with logistic regression test revealed that there are two variables that partially affect the audit opinion is Going Concern Audit Opinion Debt Default and the Previous Year. This is evidenced by the significant value of 0.00 (Debt Default) and 0.00 (Opinion Audit Prior Year) where the value is smaller than 0.05. Overall value based test Nagelkerke R Square shows that Quality Auditor, Debt Default, Opinion Shopping, Prior Year Audit Opinion and Reputation KAP is equal to +0.300 which means all the dependent variable can be explained by the independent variable by 30 percent.Keywords: Quality Auditor, Debt Default, Opinion Shopping, Audit Opinion and The Previous Year Reputation of Public Accounting firm (KAP)